The Register Of Military Discourse in Spoken Communication at the 1st Health Battalion of Kostrad Bogor and the 10th Armed Battalion of Brajamusti Bogor - Annisa; Permana, Sudarya; Failasuf, Chakam (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Communication is one of the tools used by humans to interact with each other. Everyone is involved in communication activities. In communication, there are media used, namely language. The use of language is determined by linguistic and non-linguistic factors. Communicating means conveying a message in the form of ideas, thoughts, feelings, and our will to others, expressed through language. Each community group has its own linguistic characteristics. Among the non-linguistic factors are social factors. Social factors that can influence the patterns of language use include social status, education level, age, economic status, gender, and so on. This research will discuss the specialized language that occurs in the military environment. This research aims to examine the military register in the spoken discourse used in the environment of the Health Battalion 1 Kostrad and the Armed Battalion 10 Brajamusti in Bogor. The military register, as a part of specialized language variation in military communication, plays a crucial role in creating communication efficiency, maintaining hierarchy, and building solidarity among members. This study focuses on identifying the types of registers, analyzing their functions and meanings, as well as exploring the linguistic and social factors that influence their formation. The method used is a qualitative descriptive approach with an ethnographic communication approach, employing data collection techniques such as participatory observation, in-depth interviews, and document analysis. The data were analyzed using discourse analysis methods to uncover the linguistic structure and its context of use. This study also compares the use of registers in two battalions to find similarities and differences arising from factors such as core duties, organizational structure, and communication culture of each battalion, both for TNI members and for Persit members or soldiers’ wives. The results of the study are expected to reveal the linguistic characteristics of military registers used, uncover social and pragmatic functions in military communication, and provide new insights into the role of language in supporting military professionalism and operational efficiency. In addition, this research aims to contribute a deeper understanding of linguistic studies, particularly in the realms of register and language variation. Thus, this research is expected to provide theoretical contributions to the development of applied linguistics as well as practical benefits in communication training in the military environment.